Information Politics of Traditional Medicine Research at Village Community of West Bandung District - Khairul Anwar, Rully; Rusmana, Agus (International Journal of Engineering and Technology, 2018)
This study examines the politics of information within a particular organization or social group, in this case is a rural community in West Bandung District. The political process of information includes activities on how the government creates, acquires transfers, alters, stores, and reuses information that is related to traditional medicine. Here also learned how people respond to public policy regarding traditional medicine. The method used is qualitative with data collection technique through observation, interview, documentation study, and literature study. The results show that there is a local political information activity in rural communities of West Bandung marked by the presence of traditional medicine managers, patients, the government with its regulations, and other information politics activities that led to the maintenance of traditional medicine and services, even traditionally, ie verbal and undocumented.Â